2016
DOI: 10.1007/s11606-016-3652-z
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Practitioner Autonomy and Relationships with Leadership Affect Teamwork in Primary Care Practices: a Cross-Sectional Survey

Abstract: BACKGROUND:The Nurse Practitioner (NP) workforce represents a substantial supply of primary care providers able to contribute to meeting a growing demand for care. However, controversy exists regarding the expanding role of NPs in primary care in terms of challenging the teamwork between NPs and physicians. To date, no empirical evidence exists regarding how to promote teamwork in primary care between NPs and physicians. OBJECTIVE: We investigated whether NP autonomy within primary care practices and the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
59
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 48 publications
7
59
1
3
Order By: Relevance
“…An autonomous nurse practitioner practices with a nursing philosophy and without being dependent upon medicine (Weiland, ). Recent literature reports that NPs working independently of physician oversight had greater autonomy associated with greater job satisfaction (Petersen & Way, ; Poghosyan & Liu, ; Spetz, Skillman, & Andrilla, ). This research concurs that NPs in both Ireland and Australia are independent and autonomous in their clinical work, and it is important to note that participants were primarily working in the acute hospital environment and regulation in Ireland and Australia require collaborative agreements with an identified physician.…”
Section: Discussionmentioning
confidence: 99%
“…An autonomous nurse practitioner practices with a nursing philosophy and without being dependent upon medicine (Weiland, ). Recent literature reports that NPs working independently of physician oversight had greater autonomy associated with greater job satisfaction (Petersen & Way, ; Poghosyan & Liu, ; Spetz, Skillman, & Andrilla, ). This research concurs that NPs in both Ireland and Australia are independent and autonomous in their clinical work, and it is important to note that participants were primarily working in the acute hospital environment and regulation in Ireland and Australia require collaborative agreements with an identified physician.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found a positive relationship between higher levels of professional nurse autonomy and higher levels of team work (i.e., nurses' working relationships with others) (Poghosyan & Liu 2016;Rafferty, Ball, & Aiken, 2001). Team working may be most effective when the staff involved have professional autonomy as they feel their practice is not restricted.…”
Section: Unity With Othersmentioning
confidence: 99%
“…For example, leaders within health care organisations such as practice managers or medical directors do not share information with NPs to support their care delivery or take NPs' concerns seriously (Poghosyan, Nannini, Stone, et al, 2013). Such poor organisational attributes and relationships between NPs and administrators not only negatively impact the practice of NPs but also undermine teamwork between NPs and physicians (Poghosyan & Liu, 2016).…”
mentioning
confidence: 99%